SCIENTIFIC AND PRACTICAL SIGNIFICANCE OF VALEOLOGY IN THE TRAINING OF NURSES - Rakhimova Kh. M.; Buranova N. R. (Journals Park Publishing, 2026)
This article analyzes the role and scientific and practical significance of valeology in the training of nurses. It addresses the development of healthy lifestyle skills, disease prevention, and the provision of high-quality patient care in future nurses based on a valeological approach. The importance of valeology in the educational process and its close relationship with medical practice are also substantiated.
Keywords: Valeology, nursing education, prevention, healthy lifestyle, medical care, public health, educational effectiveness.